Nutritional risk in major abdominal surgery: protocol of a prospective observational trial to evaluate the prognostic value of different nutritional scores in pancreatic surgery - Probst, Pascal; Haller, Sebastian; Dörr-Harim, Colette; Bruckner, Thomas; Ulrich, Alexis; Hackert, Thilo; Diener, Markus K.; Knebel, Phillip (JMIR Research Protocols)
Background: The influence of patients’ preoperative nutritional status on their clinical outcome has already been proven. Therefore, patients with malnutrition are in need of additional therapeutic efforts. However, for pancreatic surgery, evidence suggesting the adequacy of existing nutritional assessment scores to estimate malnutrition associated with postoperative outcome is limited. Objective: The aim of the observational trial “Nutritional Risk in Major Abdominal Surgery (NURIMAS) Pancreas” is to prospectively assess and analyze different nutritional assessment scores for their prognostic value on postoperative complications in patients undergoing pancreatic surgery. Methods: All patients scheduled to receive elective pancreatic surgery at the University Hospital of Heidelberg will be screened for eligibility. Preoperatively, 12 nutritional assessment scores will be collected and patients will be assigned either at risk or not at risk for malnutrition. The postoperative course will be followed prospectively and complications according to the Clavien-Dindo classification will be recorded. The prognostic value for complications will be evaluated for every score in a univariable and multivariable analysis corrected for known risk factors in pancreatic surgery. Results: Final data analysis is expected to be available during Spring 2016. Conclusions: The NURIMAS Pancreas trial is a monocentric, prospective, observational trial aiming to find the most predictive clinical nutritional assessment score for postoperative complications. Using the results of this protocol as a knowledge base, it is possible to conduct nutritional risk-guided intervention trials to prevent postoperative complications in the pancreatic surgical population. Trial Registration: germanctr.de: DRKS00006340; https://drks-neu.uniklinik-freiburg.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00006340 (Archived by WebCite at http://www.webcitation.org/6bzXWSRYZ) [JMIR Res Protoc 2015;4(4):e132]